1998
DOI: 10.1007/s002449900376
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dispersants on the Bioavailability of Naphthalene from the Water-Accommodated Fraction Crude Oil to the Golden-Brown Algae, Isochrysis galbana

Abstract: The golden-brown algae Isochrysis galbana, a primary producer, was used to determine the influence of the chemical dispersing agent, Corexit 9527((R)), on the bioavailability of naphthalene. Cells were exposed to laboratory preparations of either the water-accommodated fraction (WAF) of Prudhoe Bay crude oil (PBCO) or a dispersed oil (DO) mixture of PBCO and Corexit 9527 spiked with [U-14C]naphthalene. Uptake was determined by the amount of algae-associated [14C]. High-pressure liquid chromatography (HPLC) co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 26 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…It is possible that these compounds were readily taken up by the cells, resulting in a rapid decrease in water concentrations to below the detection limit of the technique. Wolfe et al (1998) also observed an initial rapid association of naphthalene with a maximum algal uptake within the first hour of exposure.…”
Section: Relevance Of Wsf Toxicitymentioning
confidence: 75%
“…It is possible that these compounds were readily taken up by the cells, resulting in a rapid decrease in water concentrations to below the detection limit of the technique. Wolfe et al (1998) also observed an initial rapid association of naphthalene with a maximum algal uptake within the first hour of exposure.…”
Section: Relevance Of Wsf Toxicitymentioning
confidence: 75%
“…Singer et al, 2000). The major constituent of WAF for the duration of the exposure period was the highly soluble bicyclic aromatic hydrocarbon naphthalene (also reported as the major constituent of WAF by Wolfe et al, 1998 andBarron et al, 1999). Previous and more sophisticated chemical analyses of WAF generated using the same technique as used in this study have additionally identified an unresolved complex mixture of PAHs (UCM) which cannot be resolved into individual compounds and the toxicity of which remains unclear (Scarlett et al, 2007;Smith et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Prolonged turbulent mixing by wind and currents results in the release of a water accommodated (or soluble) fraction (WAF) mainly comprised of naphthalene (Rossi & Anderson, 1976;Wolfe et al, 1998;Barron et al, 1999;Pollino & Holdway, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Davenport (1982) demonstrated that diatom populations are affected severely by hydrocarbon concentration. Aromatic hydrocarbons are one of the most important inhibitors of the growth of microalgae (Walker et al, 1975;Cerniglia, 1981;Wolfe et al, 1998;González et al, 2009). Their effects include immediate toxicity due to the soluble aromatic fraction, prolonged toxicity due to persistent products, and altered physical-chemical conditions below the floating oil (for example, temperature changes).…”
Section: (A) (B)mentioning
confidence: 99%